Studi Pengetahuan Pengeolaan Keuangan Pada Pengusaha Depot Air Isi Ulang di Desa Nggele Kecamatan Taliabu Barat Laut - Irmawati Loong; Abdul Hadi Sirat; Suratno Amiro (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to find out how knowledge of financial management which includes planning, recording, reporting and control is applied by the refill water depot business in Nggele Village, Northwest Taliabu District. The qualitative descriptive research method with data collection techniques carried out in this study was by conducting interviews with three informants regarding financial management which included: budget use, recording, reporting and control which were applied to three depot business owners in Nggele village. The results of this study indicate that: (1) financial planning, the three business depots in Nggele village have fully implemented financial management of financial planning for their businesses. The planned planning is planning the initial capital budget, production budget, sales budget, profit budget and cash reserves. (2) the recording of the three depot businesses has not fully recorded their business. Three of the informants kept records very simply, two other informants did not make any records in their business (3) reporting to the three depot businesses did not make financial reports in their business because the owners did not understand how to prepare financial reports; and (4) the control carried out by the three depot businesses had not been fully carried out in relation to the evaluation of their business, the informants exercised control in managing their finances with the understanding and knowledge of the owner.